Innovation Strategy as a New Product Success Factor - Marinov, Krassimir (Research Papers, 2005)
The study discusses the nature and contents of firm’s new products strategy. First peculiarities of the innovation strategy are systematized as a system of product innovation most important decisions. Approaches to its definition, used in previous research, are presented. Suggestion and reasons are given for a new definition of innovation strategy.Focus of the study is contents of the innovation strategy. Each element of the new product strategy is characterized in detail as well as interrelationships between elements. It is argued that elements of this strategy are: goals concerning new products, strategic areas of product innovation, peculiarities of new products in each strategic area, portfolio of new product projects, and innovation budget of the firm.